Global research presenteeism trends: A bibliometric analysis and knowledge mapping - Emad Shdaifat; Amira Alshowkan (International Journal of Africa Nursing Sciences)
Introduction: Absenteeism, primarily resulting from employee burnout and stress, has been recognized as a significant contributor to staff shortages and diminished productivity in organizations globally. Objective: This study conducts a bibliometric analysis of presenteeism research, systematically examining global contributions from 1975 to 2021. Methods: The Web of Science (WoS) database was chosen for this analysis. A total of 1,908 documents were examined, with a focus on countries, institutions, authors, journals, keywords, citations, and emerging topics. Data were extracted and analyzed utilizing the Bibliometrix R-package software. Results: A total of 1,908 publications were identified in this study. The predominant document type was journal articles (n = 1,711; 90 %), followed by review articles (n = 152; 8 %). These publications were disseminated across 1,908 distinct sources and collectively cited 686 references. The Journal of Occupational and Environmental Medicine emerged as the primary source of these publications, and A. Boonen was recognized as one of the most prolific authors in this field. The prevailing research themes focused on the determinants, associated factors, and predictors of presenteeism, highlighting the critical need for targeted interventions. Conclusion: The majority of the studies retrieved concentrate on the determinants, associated factors, predictors, and prevalence of presenteeism. There exists a significant need for specialized research across various settings, particularly empirical intervention studies designed to mitigate presenteeism among professionals. Trial Registration: N/A.